Spi-B alleviates food allergy by securing mucosal barrier and immune tolerance in the intestine - Ishihara, Narumi; Nakamura, Yutaka; Yakabe, Kyosuke; Komiyama, Seiga; Fujimura, Yumiko; Kaisho, Tsuneyasu; Kimura, Shunsuke; Hase, Koji (Frontiers in Allergy, 2022)
Food allergy is a type I allergic reaction induced by mast cells and is mainly activated by allergen-specific immunoglobulin (Ig)E. Spi-B is an E26-transformation-specific (Ets) family transcription factor essential for the differentiation and functional maturation of several immune cell subsets, including mast cells. However, the possible involvement of Spi-B in food allergy remains unclear. In this study, we found that Spi-B-deficient mice were highly susceptible to food allergy to ovalbumin (OVA), as indicated by the exacerbation of diarrhea and elevation of serum IgE levels. These pathological changes were associated with enhanced mast cell infiltration into the intestinal lamina propria. Activation of mast cells in the intestinal mucosa was observed in Spib−/− mice, even under physiological conditions. Accordingly, Spi-B deficiency increased the translocation of fluorescently labeled dextran from the lumen to the serum, suggesting increased intestinal permeability in Spib−/− mice. Moreover, Spib−/− mice showed defects in oral tolerance induction to OVA. These data illustrate that Spi-B suppresses the development of food allergies by controlling the activation of intestinal mast cells and by inducing immune tolerance to food allergens.